European film theory - Trifonova, Temenuga (AFI film readers., 2008)
European Film Theory explores the 'Europeanness' of European film theory, its philosophical origins, the 'culture wars' between 'Continental' and 'Analytical' film theory and philosophy, the major discursive and epistemological shifts in the history of Continental film theory, the relationship between Continental philosophy of art and philosophy of history and European film theory. Writing from a range of disciplines and perspectives, the contributors to this new volume in the AFI FILM READERS series offer fresh interpretations of European film theorists and illuminate the politica.